# Find and correct the errors in the statement: (a - 4)(a - 2) = a^{2} - 8

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

Given,

(a - 4)(a - 2) = a^{2} - 8

Solving LHS we get,

(a - 4)(a - 2)

= (a × a) + (-2) × a + (-4) × a + [(-4) × (-2)]

= a^{2 }- 2a - 4a + 8

= a^{2} - 6a + 8

But RHS is given as a^{2} - 8

Thus, L.H.S ≠ R.H.S

The correct statement is (a - 4)(a - 2) = a^{2} - 6a + 8

**Video Solution:**

## Find and correct the errors in the statement: (a - 4)(a - 2) = a² - 8

### Class 8 Maths NCERT Solutions - Chapter 14 Exercise 14.4 Question 15

**Summary:**

Find and correct the errors in the statement: (a - 4)(a - 2) = a^{2} - 8. The correct statement is (a - 4)(a - 2) = a^{2} - 6a + 8